Über die Bedeutung von Alltagsauffassungen für das Wirtschaftsgeschehen - Birger P. Priddat (Wirtschaftsdienst, 2014)
Die aktuelle Finanzkrise hat es an den Tag gebracht. Die Mehrzahl der wirtschaftlichen Akteure handelt nicht in der Form rational, wie es die ökonomische Theorie erwartet, sondern nach alltagsökonomischen Faustregeln. Rational sind diese nur insoweit, als es sich nach Auffassung der Masse vor allem in Situationen der Unsicherheit bewährt hat, bei der 'Herde' zu bleiben. Der Autor befürchtet, dass die Ökonomik das Verhalten dieser Akteure nicht versteht. – – Economics has begun to analyse its actors in a new light. Behavioural economics analyses real motives, reasons, attitudes and belief structures, individual and shared mental models, emotions, etc. The everyday behaviour of actors is generally incompatible with rational choice behaviour. Economic theory responds to this disconnect with modified models of rationality, but we have to be aware that defining rationality is aimed more at a normative conception of elegant model-building than it is at trying to explain real behaviour. 'Real actors' have models, patterns and interpretations of their own in their economic everyday lives. Thus, economic theory must begin to take into account actors operating according to rules and theories different from those of the general economic models.
Keywords: D1; D8; 330